The relationship between cytochrome P4502E1 activity and plasma fluoride levels after sevoflurane anesthesia in humans - Wandel, Christoph; Neff, Sabine; Keppler, Gudrun; Böhrer, Hubert; Stockinger, Klaus; Wilkinson, Grant R.; Wood, Margaret; Martin, Eike (Anesthesia & analgesia, 1997)
We determined whether the perianesthetic plasma fluoride levels after sevoflurane anesthesia in humans were correlated with the metabolic ratio (MR) of 6-hydroxychlorzoxazone to chlorzoxazone, an in vivo probe for cytochrome P4502E1 (CYP2E1) activity. Thirty ASA physical status I or II patients scheduled for extraabdominal surgery were randomized to a chlorzoxazone (n = 20) or a control group (n = 10). Patients in the chlorzoxazone group received 500 mg chlorzoxazone orally on the morning of the day of surgery. Chlorzoxazone and its 6-hydroxymetabolite concentrations were measured in plasma 2 h after drug administration. Anesthesia was induced with propofol, fentanyl, and atracurium intravenously and maintained with sevoflurane (inspired concentration 1-3 vol%). Plasma fluoride concentrations were determined before the induction of anesthesia, at the cessation of sevoflurane, and 2, 4, 6, 10, and 24 h thereafter. The area under the plasma fluoride concentration-time curve (AUC) was calculated up to 24 h after sevoflurane cessation. MR correlated significantly with the plasma fluoride AUC (r2 = 0.28, P < 0.025), the elimination constant calculated for the postanesthetic 10- to 24-h period (r2 = 0.30, P < 0.025), and the plasma fluoride levels 24 h after the cessation of sevoflurane (r2 = 0.48, P < 0.05). A comparison between groups indicated that the administration of chlorzoxazone itself did not alter the postanesthetic fluoride kinetics. Thus, the interindividual variability in perianesthetic plasma fluoride levels after sevoflurane anesthesia is reflected by differences in the MR of chlorzoxazone and hence is related to the interindividual variability in CYP2E1 activity. We conclude that although the predictive value is limited, this study provides a reasonable basis for examining renal function after sevoflurane anesthesia in a subgroup of patients with a high preoperative metabolic ratio of chlorzoxazone. Implications: CYP2E1 metabolizes sevoflurane as measured by the metabolic ratio of chlorzoxazone. Patients with a high ratio may be used to justify examining renal function in patients receiving sevoflurane. - (Anesth Analg 1997;85:924-30)
Gesehen am 29.04.2024